Respuestas

  • Usuario de Brainly
2012-06-06T15:35:33+02:00

Ok Sareh ahi te van

 

1)

 

5x + 3y = 425.......1

3x - 3y = 39.........2

 

Eliminado "Y" de 1 y 2

 

5x + 3y = 425.......1

3x - 3y = 39.........2

--------------

8x        = 464

x = 464/8

x = 58 ....R/. 

 

Remplazando "X" en 2

 

3(58) - 3y = 39

174 - 3y = 39

174 - 39 = 3y

135 = 3y

135/3 = y

y = 45.....R/.

 

2)

 

5x + 2y = 70......1

3x - 2y = -4.......2

 

Eliminando "Y" de 1 y 2

 

5x + 2y = 70

3x - 2y = -4

----------------

8x        = 66

x = 66/8

x = 33 /4 ....R/.

 

Remplazando "X" en 2

 

3(33/4) - 2y = -4

99/4 - 2y = -4

99/4 + 4 = 2y

(99 + 16)/4 = 2y

115/4 = 2y

(115/4)/2 = y

115/8 = y....R/.

 

Espero haberte podido ayudar